The Effect of Use of Protein Supplements on Muscle Damage - Karakus, Mustafa; Akkurt, Soner (Progress in Nutrition, 2020)
Study objectives: The purpose of this study was to examine the effect of ingested protein supplementation on muscle damage and delayed onset muscle soreness followed acute maximal weightlifting exercise. Method: Twenty-four males were included in this study who between the ages of 19-25 and were performing the physical activity for an average of 60 minutes 2 days a week. The volunteers were randomly divided into two groups as the experimental group that takes a protein supplement and control group that doesn’t take a protein supplements. Blood samples were taken from all volunteers before exercise. Followed warming, 3 sets 10 repetitions weightlifting exercise were performed at 80% 90 and 100 of pre-determined maximal weights. The diets of athletes were determined by an expert dietitian as 1 g/kg per day of all participants by dividing into three meals. In addition, the experimental group was taken protein supplement also 35 grams of whey protein (total: 1.5g/kg per day) after the lunch by dissolving in 500 ml water. The blood samples of both groups were taken at the before, immediately after, 24th, 48th, and 72nd hours after exercise at the same time of the day and the VAS scores were recorded. Results: There was no significant difference between experimental and control groups before and immediately after exercise in terms of CK and Mb values when the group effect is considered (p>0.05). When, the VAS score were examined independent from the group effect, it was observed that the values of control group were higher than the experimental group in the 2nd, 3rd, and 4th comparisons (p